A methodology for shrinkage measurement in micro-injection moulding - Annicchiarico, Daniele; Attia, Usama M.; Alcock, Jeffrey R. (Elsevier Science B.V., Amsterdam., 2013)
The aim of this paper is to provide a method for measuring shrinkage in micro injection moulded (μ-IM) parts - no standardised approach being reported as yet in the literature. This study investigates the feasibility of implementing the international standards used to investigate shrinkage in conventional (macro) moulding at the micro-scale. Following a similar experimental procedure to the relevant standards, micro-moulded polyoxymethylene (POM) specimens were produced, and the influence of processing parameters on their shrinkage was analysed using the design of experiment (DoE) approach. The analysis results showed that the methodology was capable of detecting factors that had a statistically significant effect on shrinkage at the micro-scale, in both parallel to, and normal to, the flow directions for moulding, post-moulding and total shrinkage.
Keywords: micro injection moulding; shrinkage; design of experiment.